Faktor determinan riwayat kehamilan dan kelahiran sebagai penyebab stunting - Masayu Dian Khairani; Kusmiyati Tjahjono; Ali Rosidi; Ani Margawati; Etika Ratna Noer (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Stunting is a condition of failure or a child's growth process that is not following their age. Many factors can cause children to experience stunting both in terms of health and outside health, such as economic conditions, nutritional status experienced by mothers during pregnancy, malnutrition, and improper feeding and care early in life. The study aimed to determine pregnancy and birth history as risk factors for stunting in children aged 24-59 months. The study used a case-control design, with the number of subjects being 176 children, calculating subjects using total sampling techniques on case subjects and matching on control subjects. The research was conducted at the Pangkalan Balai Health Center, Banyuasin Regency, South Sumatra, in 2022. Data was collected for one month and then analyzed using the chi-square test and Logistic Regression. The results showed that parental income (p= 0,034; OR= 2,571), early marriage (p= 0,001; OR= 2,760), maternal age at pregnancy (p= 0,003; OR= 2,692), nutritional status at pregnancy (p=0,020; OR=2,080), birth length (p= 0,001; OR= 6,633) and birth weight (p= 0,044; OR= 3,632) are risk factors for stunting. The most influential determinant factor was the birth length. Conclusion, parental income, early marriage, age at risk of pregnancy, nutritional status of pregnant women, birth length, and birth weight are risk factors for stunting in children aged 24-59 months at Pangkalan Balai Health Center.